2012
DOI: 10.2527/jas.2011-4232
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation at various temperatures of bovine viral diarrhea virus in beef derived from persistently infected cattle1

Abstract: Bovine viral diarrhea virus (BVDV) is a pestivirus that is enzootic in most cattle populations throughout the world. This virus is present throughout the body of persistently infected (PI) cattle. Previous research has not assessed the cooking temperature at which BVDV in meat from PI cattle can be inactivated. Therefore, muscle tissue from 6 PI cattle was harvested, refrigerated, frozen, and heated to various internal temperatures. The concentration of virus present was determined by virus isolation. Average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…BVDV is not considered zoonotic, although the ability of BVDV to replicate in human cell lines has been reported in some studies and there are limited reports of detection of virus, viral RNA or antigen in human samples (Giangaspero et al., ; Walz et al., ; Bratcher et al., ).…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…BVDV is not considered zoonotic, although the ability of BVDV to replicate in human cell lines has been reported in some studies and there are limited reports of detection of virus, viral RNA or antigen in human samples (Giangaspero et al., ; Walz et al., ; Bratcher et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…Observational studies on the impact of infection with BVDV on health and production parameters have been reviewed in the EU Thematic network on control of BVDV (2001) and the results are reproduced below (Table 3). BVDV is not considered zoonotic, although the ability of BVDV to replicate in human cell lines has been reported in some studies and there are limited reports of detection of virus, viral RNA or antigen in human samples (Giangaspero et al, 1997;Walz et al, 2010;Bratcher et al, 2012).…”
Section: Acute (Transient) Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…During aging period, these factors can affect the infectivity of enteric viruses (Jończyk, Klak, Międzybrodzki, & Górski, ). It was demonstrated that Crimean‐Congo hemorrhagic fever virus (CCHFV) does not survive in matured meat after aging time but according to Bratcher et al () aging of meat for 21 day at 4 °C cannot use to diminish the potential for transmission of Bovine viral diarrhea virus (BVDV) (Bratcher et al, ; Public Health Agency of Canada, ; Yadollahie, ).…”
Section: Introductionmentioning
confidence: 99%
“…matured meat after aging time but according to Bratcher et al (2015) aging of meat for 21 day at 4 8C cannot use to diminish the potential for transmission of Bovine viral diarrhea virus (BVDV) (Bratcher et al, 2015;Public Health Agency of Canada, 2010;Yadollahie, 2012).…”
mentioning
confidence: 99%